Validation of the flexibility component of the AAHPERD functional fitness assessment in brazilian older adults. 10.5007/1980-0037.2011v13n6p455 - Daniel Rogério Petreça; Tania R. Bertoldo Benedetti; Diego Augusto Santos Silva (Universidade Federal de Santa Catarina, 2011)
Flexibility is an indispensable component of the ability to carry out activities of daily living. The flexibility test proposed by the American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD) is easy to administer and requires little equipment. Thus, the present study sought to ascertain the validity of the flexibility component of the AAHPERD Functional Fitness Assessment in Brazilian older adults. The study sample comprised 330 subjects (278 women and 52 men), with a mean age of 69.45+6.19 years, who took part in a physical activity program for older adults. The Leighton Flexometer was chosen as a comparator instrument. The Pearson correlation coefficient (r), simple linear regression, and Bland-Altman plots were used for statistical analysis. The correlation between AAHPERD Functional Fitness Assessment and Leighton flexometer findings was r = 0.93 and r = 0.86 (p <0.01) for males and females respectively. The AAHPERD Functional Fitness Assessment explained 74.3% of variance in Leighton flexometer findings in female participants and 86.6% in male participants. We conclude that the flexibility component of the AAHPERD Functional Fitness Assessment provides adequate estimation of lumbar and hip flexibility in Brazilian older adults.